2000
DOI: 10.1093/clinchem/46.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Free or Complexed Prostate-specific Antigen (PSA) to Total PSA: Which Ratio Improves Differentiation between Benign Prostatic Hyperplasia and Prostate Cancer?

Abstract: Background: The aim of this study was to compare the diagnostic utility of a new assay that measures all forms of prostate-specific antigen complexed (cPSA) to serum proteins except α2-macroglobulin with the assay of free PSA (fPSA) and the corresponding ratios to total PSA (tPSA) to improve the differentiation between benign prostatic hyperplasia (BPH) and prostate cancer (PCa). Methods: Serum samples were collected from 91 men without prostate disease and with normal digital rectal examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 23 publications
5
31
1
Order By: Relevance
“…The speci®city of fPSA% was superior to that of tPSA and cPSA for the cutoff values providing sensitivities between 80 and 90% [8]. We performed analogous measurements and came to similar conclusions [9]. These results are partly in contrast to those of Brawer et al [10,11] who described good results with cPSA measurements alone.…”
Section: Introductionsupporting
confidence: 76%
“…The speci®city of fPSA% was superior to that of tPSA and cPSA for the cutoff values providing sensitivities between 80 and 90% [8]. We performed analogous measurements and came to similar conclusions [9]. These results are partly in contrast to those of Brawer et al [10,11] who described good results with cPSA measurements alone.…”
Section: Introductionsupporting
confidence: 76%
“…Although no study has been conclusive, some have shown promising results with an increased specificity over tPSA in the detection of prostate cancer while other studies have shown an equivalence to the f/t PSA. [15][16][17][18][19][20] There also is a cost advantage in using cPSA. In comparison to the measurement of the f/t PSA, which requires two assays, the measurement of cPSA requires only one assay.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have shown that fPSA/tPSA or tPSA/cPSA ratios improve specificity in the detection of prostate cancer. [12][13][14][15][16][17] Our previous study also demonstrated that fPSA/tPSA and tPSA/cPSA ratios are superior to tPSA in detecting prostate cancer. [18][19][20] In the present study, we determine whether the different molecular forms of prostate-specific antigen and other PSA variables can predict prostate cancer in men undergoing repeat prostate needle biopsy.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, serum from patients with prostate cancer contains a higher proportion of PSA complexed with a 1-antichymotrypsin than does serum from patients with BPH. [12][13][14][15][16][17] Complexed PSA assay (cPSA) thus seems a fruitful approach to diagnosing prostate cancer. Several investigators have shown that fPSA/tPSA or tPSA/cPSA ratios improve specificity in the detection of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%